Efecto de la autohemoterapia sobre los parámetros productivos en diferentes razas comerciales de conejos (Oryctolagus cuniculus). - Romero Pérez, Andrea Marcela (2025)
This experimental research was carried out with the purpose of evaluating productive parameters and was developed within the seedling project "Productive evaluation of minor species" in the animal production program of the Veterinary Medicine career of the Faculty of Agricultural Sciences of the Technical University of Babahoyo located at kilometer 1.5 of the Babahoyo – Montalvo road in the province of Los Ríos. It was executed through three treatments against a control treatment, each treatment will be made up of 4 treatments and 3 repetitions giving a total of 12 Experimental Units, which will be made up of 4 animal units with a total population of 48 animals throughout the investigation. With the inclusion of the autohemotherapy technique in doses of 0.05 ml, 0.10 ml and 0.15 ml. The research showed that the Belier breed rabbits started with an average weight of 406,25 g and the Rex breed with 377,33 g. When evaluating the treatments, it was observed that the Belier under treatment T3 reached the highest weight (8033 g), while the Rex with T3 reached 3944 g. The lowest weights were recorded in treatment T0 for both breeds (7541.33 g in Belier and 3049 g in Rex). Regarding weight gain, the Belier with T1 increased 7621.33 g and the Rex with T3, 3592.67 g, with T0 being the one with the lowest gain. Regarding the immunological aspect, the initial HMC was 46.27% for the Belier and 43.33% for the Rex. Under T2 treatment, both improved significantly (Belier: 51.30%, Rex: 51.23%), while T0 presented the lowest value (38.27%). These results show that autohemotherapy significantly improves productive and immunological parameters in both rabbit breeds, especially compared to the control group (T0).